Is ghrelin a natural anti-microbial agent? - Aydin, Sueleyman; Geckil, Hikmet; Kilic, Nermin; Erman, Fazilet; Kilic, Sueleyman Sirri; Yesilada, Oezfer (Tubitak Scientific & Technological Research Council Turkey, 2008)
[Abstract Not Available]